A study of kinetics and successive sorption/desorption of Zn and Cd uptake onto iron-modified zeolite. (2nd January 2018) - Ugrina, Marin; Medvidović, Nediljka Vukojević; Perić, Jelena; Trgo, Marina
Abstract: The sorption properties of iron-modified zeolite (IMZ) and the kinetics of zinc and cadmium uptake by the IMZ were investigated by the batch method. Two kinetic stages were observed, fast uptake up to 240 min, followed by slow uptake up to equilibrium. Kinetic results were fitted to the reaction and diffusion kinetic models, which indicated that intra-particle diffusion was the rate-limiting step. The Vermeulen's approximation model was used to predict the quantity of Zn and Cd ions removed per gram of IMZ. The results of the successive sorption and desorption of Zn and Cd ions, with different electrolyte solutions, showed the best desorption efficiency with sodium salt solutions. Four successive repetitions of the sorption/desorption cycles showed a small difference between the amount of sorbed and desorbed Zn and Cd ions from the second to the fourth cycle. This indicates excellent sorption/regeneration properties of the IMZ.